Micropropagation of waterpear (Sechium edule Jacq. S.W.) from vegetative shoots. - Abdelnour Esquivel, Ana (2006)
Waterpear (Sechium edule) isan important source of revenue for the exporting countries,being Costa Rica the leading producer. Among the mainlimiting factors for its production are the planting materials,traditionally the seed, that because of its nature it does notallow the production of morphologically homogeneous fruits(color, shape and epidermal texture), which results in highpercentages of rejected fruits at the packing plant. Theestablishment of a protocol for vegetative propagation of thisspecies will help to solve the heterogeneity problems. Thepresent research was directed to develop a micropropagationprotocol from shoots. The effect of various desinfectants andconcentration of growth regulators during the in vitroestablishment, multiplication and rooting phases wereevaluated. Desinfections with 4% calcium hypochloriteallowed the highest percentage of aseptically establishedexplants under in vitro conditions. There was also observedthat during the following phases of micropropagation therequirements of growth regulators were very low (0.1 mgL-1BA during bud sprouting and 0.1 to 0.2 mgL-1 AIB duringrooting) or were not required (microcutting multiplication).